Justice in Times of Crisis - Boylan, Michael (2013)
In the Wake of Terror: Medicine and Morality in a Time of Crisis. Edited by Jonathan D. Moreno. Cambridge, MA: M.I.T. Press, 2003. Pp. 229. In the United States, we are currently consumed by the threat of future terrorism. Our barometer of danger vacillates between different colored assessments of how likely it is that some catastrophic event is about to occur. Is this merely hype, or do we face an imminent threat? To some degree, the answer to that question is irrelevant. Guided by the precautionary principle, most would argue that the nation must prepare itself for the worst case scenario. Most of the current literature on our response to terrorism examines policy initiatives that purportedly seek to protect the public good. These policy initiatives aim to strike the proper balance between achieving the directives of the general will and sufficiently protecting individual liberties. To date, most scholars and public thinkers have been primarily concerned with assessing the best way to strike this difficult balance. As important as such works are, a crucial component of our national preparation against terrorism has not yet been adequately addressed: namely, the involvement of the medical community. The medical community must be viewed as an essential part of this effort since they are among the first responders in times of emergency. Yet, this has not been a particularly fruitful area of scholarship, perhaps because many assume that plans already in existence for natural disasters will be sufficient to address any incident of terrorism. Such logic is mistaken. Terrorist incidents and the preparation for such incidents constitute new challenges for the national health care system. For this reason, the threat of terrorism should prompt us to reconsider some of the ethical questions posed by health care delivery in times of crisis